Cytotoxicity and apoptotic induction of glucoraphenin-isothiocyanate against human hepatocellular carcinoma (HepG2) cell line - Kntayya, Saie Brindha (2017)
Glucosinolates are natural compounds of plants. These compounds have been actively studied over the past years particularly due to their chemopreventive properties as well as their future potential usage in the chemotherapeutic field, as thus far, there has been no found cure to cancer. This study focuses on one out of an estimated 200 different types of existing glucosinolates, namely glucoraphenin (GRE). This glucosinolate is found to be present in high quantities in radish and in other cruciferous vegetables (Brassicaceae). GRE which was extracted from the seeds of Raphanus sativus L. (Kaiware daikon), was hydrolysed with myrosinase enzyme to form sulphoraphene (GRE-ITC). This isothiocyanate has revealed significant anticancer properties in previous studies. The aim of this study is to determine the cytotoxicity and further evaluate the apoptotic induction of GRE-ITC specifically against the human hepatocellular carcinoma cell line (HepG2). The findings show that GRE-ITC produced a positive cytotoxic effect on HepG2 cells with IC50 values of 47.79±0.48 μM, 47.55±0.48 μM and 45.27±0.89 μM in comparison to cisplatin (positive control) with IC50 values of 7.49±0.12 μM, 1.98±0.04 μM and 0.66±0.0 μM for incubation periods of 24, 48 and 72 hours, respectively. The intact GRE however showed no cytotoxic effects against HepG2 cells at all incubation periods. All morphological tests for apoptotic evaluation using AOPI, DAPI and TUNEL staining assay indicated clear apoptotic cell characteristics i.e. early and late apoptosis, cell shrinkage, membrane blebbing, chromatin condensation, and nuclear fragmentation. The Annexin V-FITC assay revealed significant (p<0.05) increases in early and late apoptosis in the GREITC treated HepG2 cells up to 72 hours incubation compared to the control HepG2 cells. The caspase activity investigation showed significant (p<0.05) increase of caspases -3/7 and -9 while caspase -8 demonstrated a decline in activity. Significant (p<0.05) inhibition of cell proliferation was indicated by cell cycle arrest at the Sub G0/G1 phase as compared to the G0/G1, G2+M and S phases. The overall results from this study indicate clear cytotoxic and apoptotic effects of GRE-ITC against HepG2 cells in vitro.